Quality of Life in Iranian Breast Cancer Survivors and Affecting Factors: A Review Article - Zaker, Mohammad-Reza; Hazrati-Marangaloo, Afshin; Hosseini, Seyede-Roghayeh (Asian Pacific Journal of Environment and Cancer, 2019)
Introduction: The breast cancer is the first common cancer among Iranian women, accounting for 24.4% of all cancers. With the improvement in disease‑free survival with advanced treatment modalities, question of quality of life (QOL) arises. The aim of the present review was assessment QOL of Iranian women with cancer breast and affecting factors. Methods: This study is a review article in which articles about Breast cancer were searched in databases such as Scopus, SID, Magiran, Google Scholar, Pubmed, IranMedex, ScienceDirec from key words of Cancer Brest, Quality of Life, Affecting Factor and Iran were used to search. Results: Twenty-eight studies from 2008 to 2018 on the quality of life of 2226 patients with breast cancer in Iran were conducted. In these studies, five different questionnaires QLQ-C30, SF-36, Ferrans & Power, QLQ-BR23, WHO-QOL 26 to check the quality of life patients were used. Conclusion: Breast cancer affects the quality of life of the patients and reduces it. Psychological and financial support and exercise and health for women experiencing breast cancer diagnosis can have been a positive impact on the disease and the patient’s compliance with the complications of the disease and the treatments.